Upper limb muscle overgrowth with hypoplasia of the index finger: a new over-growth syndrome caused by the somatic PIK3CA mutation c.3140A>G - Mohammad M. Al-Qattan; Ali Hadadi; Abdullah M. Al-Thunayan; Ahmed A. Eldali; Mohammed A. AlBalwi (BMC, 2018)
Abstract Background Scientists have previously described an overgrowth syndrome in Saudi patients and named it 'Upper limb muscle overgrowth with hypoplasia of the index finger' syndrome. Case presentation We describe a new case and document that the syndrome is caused by the somatic PIK3CA mutation c.3140A>G, p.His1047Arg. We also recruited one of the previously reported cases and found the same somatic mutation in the affected muscles. A wider classification of 'PIK3CA-related pathology spectrum' is presented which includes cancer, benign skin lesions/tumors, Cowden syndrome, isolated vascular malformations and various overgrowth syndromes. The latter entity is sub-divided into 3 sub-groups: overgrowth with brain involvement, overgrowth with multiple lipomatosis, and overgrowth without brain involvement/multiple lipomatosis. Conclusion Our literature review indicated that "upper limb muscle overgrowth with hypoplasia of the index finger" is not as rare as previously thought to be. This overgrowth syndrome is unique and is caused by the somatic PIK3CA mutation c.3140A>G.